Real-time detection of extravasation events of diagnostic and therapeutic radiopharmaceuticals in oncology - Noemi Cucurachi; Federica Fioroni; Elisa Grassi; Nicola Panico; Laura Verzellesi; Andrea Botti; Alessandro Fraternali; Massimo Roncali; Rexhep Durmo; Angelina Filice; Mauro Iori (PLoS ONE, 2026)
Background Radiopharmaceutical extravasation—when injected activity remains in soft tissue rather than entering the bloodstream—can compromise quantification in positron emission tomography/computed tomography (PET/CT) and, in therapeutic settings, deliver high local radiation doses. These effects may lead to inaccurate Standardized Uptake Value (SUV) measurements, potential misdiagnosis, repeat examinations, and to avoid patient risk. We assessed a simple, real-time approach for detecting extravasation during administration to enable immediate management and quantitative correction. Results Real-time monitoring with portable gamma detectors was applied to 885 diagnostic PET examinations ( 18 F-FDG, 68 Ga-DOTATOC/TATE, 68 Ga-PSMA-11) and 15 administrations of 177 Lu-DOTATATE therapy. In the diagnostic cohort, 53 extravasation events were identified and confirmed on PET images. Analysis of dose-rate–time curves yielded practical thresholds for extravasation detection: Δp in nor = 0.30 and ΔR t = 388 µSv/h. A statistically significant association was observed between SUV correction factors and specific curve parameters, enabling prospective adjustment of SUV before image interpretation. In the therapeutic cohort, one extravasation was observed, with an estimated absorbed self-dose of 11.6 Gy to the affected region. The monitoring enabled timely intervention that limited unnecessary exposure and workflow disruption. Feasibility analyses indicated that, for diagnostic procedures, a single detector can be sufficient for reliable extravasation identification and for deriving SUV correction factors. Conclusions A real-time, detector-based strategy can identify radiopharmaceutical extravasation during injection, support immediate mitigation, and preserve diagnostic accuracy by allowing early SUV correction. In therapeutic applications, it can reduce risk by prompting management of rare but consequential events. The operational simplicity, low cost, and effectiveness demonstrated across both diagnostic and therapeutic scenarios support integration of this approach into routine clinical practice, with the added practicality that a single detector appears adequate for diagnostic workflows.